2015
DOI: 10.3945/ajcn.115.113886
|View full text |Cite
|
Sign up to set email alerts
|

High-dose vitamin D3 in adults with pulmonary tuberculosis: a double-blind randomized controlled trial

Abstract: A high-dose vitamin D3 regimen safely corrected vitamin D deficiency but did not improve the rate of sputum Mtb clearance over 16 wk in this pulmonary tuberculosis cohort. This trial was registered at clinicaltrials.gov at NCT00918086.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 29 publications
4
104
0
5
Order By: Relevance
“…Indeed, previous studies have shown an inverse correlation between 25(OH)D concentrations and LDL cholesterol with an independent effect of solar UV radiation (32 (39)(40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, previous studies have shown an inverse correlation between 25(OH)D concentrations and LDL cholesterol with an independent effect of solar UV radiation (32 (39)(40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 96%
“…In the UV group, n = 58 at months 0-2, n = 53 at month 3, n = 46 at month 4, n = 42 at month 5, and n = 40 at month 6. D3, vitamin D 3 ; UV, narrow-band UV type B; 25(OH)D, 25-hydroxyvitamin D. 44 oral vitamin D would likely have a stronger effect on enterohepatic metabolism. Another plausible explanation for the disparate actions of the 2 modes of raising 25(OH)D concentrations is that UVB exposure generates bioactive molecules that, similar to vitamin D, can exert systemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies examining the effect of vitamin supplementation on pulmonary diseases have shown diverse results. The response to tuberculosis treatment with and without vitamin D was not different (14,15). Even though low vitamin D levels was associated with impaired lung function and to an inadequate response to treatment in patients with asthma, the addition of vitamin D did not modify the progression of the disease, compared to controls (16,17).…”
mentioning
confidence: 86%
“…При этом ТТ-генотип был ассоциирован с более тяжелым течением заболевания по сравнению с СС-и ТС-вариантами [24]. Исследование TagI поли-морфизма гена VDR у взрослых, страдающих легочным туберкулезом, показало преобладание аллеля Т в груп-пе больных, соотношение генотипов ТТ, Тt и tt соста-вило соответственно 29, 45 и 26% [25]. При исследова-нии влияния TagI и FokI полиморфизмов на скорость очищения мокроты у больных легочным туберкулезом при введении им добавок витамина D было выявлено, что при генотипе CC TagI полиморфизма скорость очи-щения мокроты выше (р=0,02), чем при других вариан-тах генотипа данного полиморфизма.…”
Section: обзоры литературыunclassified